Application of solid waste composition

By using a solid waste composition composed of red mud and coal gangue, combined with the addition of polyvinyl alcohol and nitric acid, an efficient ammonia oxidation catalyst for motor vehicle exhaust was prepared, which solved the problem of insufficient catalyst synthesis in the prior art and achieved low Cost, efficient NH3 adsorption and storage effects.

CN119425696APending Publication Date: 2025-02-14CHINA AUTOMOTIVE TECH & RES CENT CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411514945.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has not yet been studied for the synthesis of ammonia exhaust catalysts for motor vehicles, and it is difficult to effectively solve the problems of adsorption and storage of NH3 in motor vehicle exhaust.

Method used

Using a solid waste composition composed of red mud and coal gangue as the catalyst matrix, a solid waste composition with high porosity and iron oxide active sites are prepared by adding polyvinyl alcohol and nitric acid through ball milling, drying, mixing, sintering and impregnation. catalyst.

Benefits of technology

This method can not only reduce the raw material cost during catalyst synthesis and save mineral resources, but also effectively adsorb NH3 molecules, improve the pollution status of solid waste, and achieve the goal of "using waste to control waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425696A_ABST
    Figure CN119425696A_ABST
Patent Text Reader

Abstract

The invention provides an application of a solid waste composition, the solid waste composition contains two solid wastes of red mud and coal gangue, can adsorb NH3 molecules, is used for preparing a motor vehicle exhaust ammoxidation catalyst, can reduce the raw material cost for synthesizing the catalyst, saves mineral resources, and has a good application prospect. And a research basis is provided for improving the solid waste pollution condition and realizing the national strategic thought of treating waste with waste in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field related to adsorbents, in particular to the application of a solid waste composition. Background Art

[0002] Red mud is an industrial solid waste discharged from the industrial aluminum production process. About 1.0 to 1.8 tons of red mud are discharged for every ton of aluminum oxide produced. With the development of circular economy, solid waste is called "resources placed in the wrong place". Therefore, the treatment and resource utilization of red mud has become an urgent problem to be solved in building a harmonious ecological environment.

[0003] Using red mud to prepare ammonia oxidation catalyst for motor vehicle exhaust is an effective way to solve solid waste pollution. The pretreated red mud mainly contains alumina, iron oxide, silicon dioxide, titanium dioxide and other substances, which are conducive to the formation of γ-Al 2 O 3 , mullite, rutile and other materials have a certain porosity and stable phase structure, which effectively promotes the catalytic reaction between the active components of iron oxide and the exhaust gas components. At the same time, red mud can obtain a high specific surface area after calcination. Given this feature, the synthesized catalytic material is more suitable for NH 3 The adsorption is very effective, which is conducive to the adsorption and storage of pollutants and their high-temperature release and conversion. It is very useful for solving the problem of NH 3 The problem of excessive cold machine emissions has a certain effect.

[0004] At present, the research on ammonia oxidation of motor vehicle exhaust is generally carried out by adsorption capture and catalytic oxidation to achieve NH 3 For the conversion of ammonia into carbon dioxide, catalysts are roughly divided into three types of materials: precious metals, transition metal oxides and composite oxides. Although there have been reports on the preparation of catalysts using red mud solid waste, the research on catalysts for synthesizing motor vehicle ammonia exhaust is still insufficient. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an application of a solid waste composition.

[0006] The technical solution adopted by the present invention is:

[0007] A solid waste composition in adsorbing NH 3 In molecular applications, the effective components of the solid waste composition are composed of red mud and coal gangue, wherein the mass ratio of red mud to coal gangue is (0.5-1): (0.2-1).

[0008] Preferably, in the application of the above-mentioned solid waste composition, the mass ratio of red mud to coal gangue in the solid waste composition is (0.5-0.8):(0.2-0.5).

[0009] Preferably, in the application of the above-mentioned solid waste composition, the solid waste composition further comprises polyvinyl alcohol and nitric acid.

[0010] Preferably, the application of the above-mentioned solid waste composition is that the solid waste composition is prepared by the following method:

[0011] (1) Red mud is placed in a ball mill, and 0.03-0.05 mol / L of dilute sulfuric acid is added, with a weight ratio of red mud to dilute sulfuric acid of 1:4-1:6. After stirring for 3-4 hours, the precipitate is filtered and washed with water, and dried at a constant temperature of 100-110° C. for 5-6 hours. After drying, the precipitate is ground and sieved through a 1000-mesh standard sieve; at the same time, the coal gangue is crushed and ball-milled to be powdered, and then sieved through a 1000-mesh standard sieve, and dried at a constant temperature of 100-110° C. for 5-6 hours;

[0012] (2) weighing red mud and coal gangue raw material powders according to the raw material mass ratio of (0.5-1):(0.2-1) and placing them in an Eirich intensive mixer, and then gradually adding a polyvinyl alcohol aqueous solution with a concentration of 1-5wt% to the mixed raw materials, and the ratio of the solution volume to the raw material mass is (50-100):(0.5-1) in mL / g. After the ceramic raw material balls are formed, they are dried at 30-50°C and sieved through a 320-400 mesh standard sieve. Then, the dried and sieved raw material balls are sintered at a constant temperature of 600-800°C for 2-3 hours to prepare a catalyst matrix;

[0013] (3) The catalyst substrate is placed in a nitric acid aqueous solution with a concentration of 0.01 to 0.03 mol / L, and is stirred and immersed in a water bath at 40 to 60° C. for 2 to 3 hours, wherein the ratio of the mass of the catalyst substrate to the volume of the nitric acid aqueous solution is 1:(10 to 20) in terms of g / ml;

[0014] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 8-12 hours.

[0015] Preferably, the application of the above-mentioned solid waste composition is that the solid waste composition is prepared by the following method:

[0016] (1) Red mud is placed in a ball mill, 0.04 mol / L of dilute sulfuric acid is added, and the weight ratio of red mud to dilute sulfuric acid is 1:5. After stirring for 4 hours, the precipitate is filtered and washed with water, and dried at a constant temperature of 100-110° C. for 6 hours. After drying, it is ground and sieved through a 1000-mesh standard sieve; at the same time, the coal gangue is crushed and ball-milled into powder, and then sieved through a 1000-mesh standard sieve, and dried at a constant temperature of 100-110° C. for 6 hours;

[0017] (2) Weighing red mud and coal gangue raw material powders according to the raw material mass ratio (0.5-0.8): (0.2-0.5) and placing them in an Eirich intensive mixer, gradually adding a 3wt% polyvinyl alcohol aqueous solution to the mixed raw materials, and the ratio of the solution volume to the raw material mass is 75:1 in mL / g. After the ceramic raw material balls are formed, they are dried at 30-50°C and sieved through a 400-mesh standard sieve. Then, the dried and sieved raw material balls are sintered at a constant temperature of 600-800°C for 3 hours to prepare a catalyst matrix;

[0018] (3) The catalyst substrate is placed in a 0.02 mol / L nitric acid aqueous solution, stirred and immersed in a water bath at 40-60° C. for 2-3 hours, and the ratio of the mass of the catalyst substrate to the volume of the nitric acid aqueous solution is 1:15 in g / ml;

[0019] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h.

[0020] Application of the solid waste composition in the preparation of ammonia oxidation catalyst for motor vehicle exhaust.

[0021] The beneficial effects of the present invention are:

[0022] The solid waste composition comprises two solid wastes, red mud and coal gangue, which can absorb NH 3 Molecules used to prepare ammonia oxidation catalysts for motor vehicle exhaust can not only reduce the cost of raw materials spent on synthesizing catalysts and save mineral resources, but also provide a research basis for improving solid waste pollution in the future and realizing the national strategic idea of ​​"using waste to treat waste". Specifically:

[0023] 1. The main raw materials used are red mud, coal gangue, polyvinyl alcohol and nitric acid, which have the advantages of low cost and waste treatment, and are suitable for large-scale production and application;

[0024] 2. The prepared solid waste composition has high porosity and more iron oxide active sites as an ammonia oxidation catalyst, 3 The molecules have strong adsorption capacity;

[0025] 3. Polyvinyl alcohol acts as a stabilizer and coupling agent. It promotes the coupling of aluminum source in red mud and iron source in coal gangue, avoiding the problem of structural agglomeration and reduced activity caused by rapid oxidation. Nitric acid acts as a surfactant. At the same time, the introduction of nitric acid can effectively decompose organic C and N impurities in red mud and coal gangue, reducing the impact of a large amount of gas generated by combustion at 350-400°C on the catalyst matrix structure.

[0026] 4. The preparation method has simple process, convenient operation, low requirements on production equipment, simple composition, and is conducive to later recycling and reuse. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the NH3-TPD test spectrum of the catalyst.

[0028] Figure 2 This is the ammonia gas desorption spectrum of the catalyst. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0030] Example 1

[0031] A solid waste composition is prepared by the following method:

[0032] (1) Weighing red mud and placing it in a ball mill, adding 0.04 mol / L dilute sulfuric acid, with the ratio of powder to solution being 1:5, stirring for 4 hours, filtering the precipitate, washing it with water, and drying it at a constant temperature of 100-110° C. for 6 hours. After drying, grinding it and sieving it through a 1000-mesh standard sieve;

[0033] (2) Weighing red mud powder and placing it in an Ailixu high-power mixer, continuously adding a 3 wt% polyvinyl alcohol aqueous solution, the solution to powder ratio is 75:1 in mL / g, so as to process it into ceramic raw material balls, and then drying the ceramic raw material balls at 30-50° C. and sieving them through a 400-mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800° C. for 3 hours to prepare a catalyst matrix;

[0034] (3) Weighing the catalyst substrate and placing it in a 0.02 mol / L nitric acid aqueous solution, stirring and immersing it in a water bath at 40-60° C. for 2 h, the mass ratio of the substrate to the volume of the nitric acid aqueous solution being 1 g:15 ml in g / ml;

[0035] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h to obtain a motor vehicle exhaust ammonia oxidation catalyst prepared using red mud.

[0036] Example 2

[0037] A solid waste composition is prepared by the following method:

[0038] (1) Weighing red mud and placing it in a ball mill, adding 0.04 mol / L dilute sulfuric acid, with the ratio of powder to solution being 1:5, stirring for 4 hours, filtering the precipitate, washing it with water, and drying it at a constant temperature of 100-110° C. for 6 hours. After drying, grinding it and sieving it through a 1000-mesh standard sieve; at the same time, crushing and ball-milling the coal gangue into powder, sieving it through a 1000-mesh standard sieve, and drying it at a constant temperature of 100-110° C. for 6 hours;

[0039] (2) Weighing red mud and coal gangue powder (the proportion of coal gangue added is 5% of the total amount) and placing them in an Ailixu high-power mixer, continuously adding a 3wt% polyvinyl alcohol aqueous solution, the ratio of solution to powder is 75:1 in mL / g, so as to process them into ceramic raw material balls, and then drying the ceramic raw material balls at 30-50°C and sieving them through a 400-mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800°C for 3h to prepare a catalyst matrix;

[0040] (3) Weighing the catalyst substrate and placing it in a 0.02 mol / L nitric acid aqueous solution, stirring and immersing it in a water bath at 40-60° C. for 2 h, the mass ratio of the substrate to the volume of the nitric acid aqueous solution being 1 g:15 ml in g / ml;

[0041] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h to obtain a motor vehicle exhaust ammonia oxidation catalyst prepared using red mud.

[0042] Example 3

[0043] A solid waste composition is prepared by the following method:

[0044] (1) Weighing red mud and placing it in a ball mill, adding 0.04 mol / L dilute sulfuric acid, with the ratio of powder to solution being 1:5, stirring for 4 hours, filtering the precipitate, washing it with water, and drying it at a constant temperature of 100-110° C. for 6 hours. After drying, grinding it and sieving it through a 1000-mesh standard sieve; at the same time, crushing and ball-milling the coal gangue into powder, sieving it through a 1000-mesh standard sieve, and drying it at a constant temperature of 100-110° C. for 6 hours;

[0045] (2) Weighing red mud and coal gangue powder (the proportion of coal gangue added is 10% of the total amount) and placing them in an Ailixu high-power mixer, continuously adding a 3wt% polyvinyl alcohol aqueous solution, the ratio of solution to powder is 75:1 in mL / g, so as to process them into ceramic raw material balls, and then drying the ceramic raw material balls at 30-50°C and sieving them through a 400-mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800°C for 3h to prepare a catalyst matrix;

[0046] (3) Weighing the catalyst substrate and placing it in a 0.02 mol / L nitric acid aqueous solution, stirring and immersing it in a water bath at 40-60° C. for 2 h, the mass ratio of the substrate to the volume of the nitric acid aqueous solution being 1 g:15 ml in g / ml;

[0047] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h to obtain a motor vehicle exhaust ammonia oxidation catalyst prepared using red mud.

[0048] Example 4

[0049] A solid waste composition is prepared by the following method:

[0050] (1) Weighing red mud and placing it in a ball mill, adding 0.04 mol / L dilute sulfuric acid, with the ratio of powder to solution being 1:5, stirring for 4 hours, filtering the precipitate, washing it with water, and drying it at a constant temperature of 100-110° C. for 6 hours. After drying, grinding it and sieving it through a 1000-mesh standard sieve; at the same time, crushing and ball-milling the coal gangue into powder, sieving it through a 1000-mesh standard sieve, and drying it at a constant temperature of 100-110° C. for 6 hours;

[0051] (2) Weighing red mud and coal gangue powder (the proportion of coal gangue added is 20% of the total amount) and placing them in an Ailixu high-power mixer, continuously adding a 3wt% polyvinyl alcohol aqueous solution, the ratio of solution to powder is 75:1 in mL / g, so as to process them into ceramic raw material balls, and then drying the ceramic raw material balls at 30-50°C and sieving them through a 400-mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800°C for 3h to prepare a catalyst matrix;

[0052] (3) Weighing the catalyst substrate and placing it in a 0.02 mol / L nitric acid aqueous solution, stirring and immersing it in a water bath at 40-60° C. for 2 h, the mass ratio of the substrate to the volume of the nitric acid aqueous solution being 1 g:15 ml in g / ml;

[0053] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h to obtain a motor vehicle exhaust ammonia oxidation catalyst prepared using red mud.

[0054] Example 5

[0055] A solid waste composition is prepared by the following method:

[0056] (1) Weighing red mud and placing it in a ball mill, adding 0.04 mol / L dilute sulfuric acid, with the ratio of powder to solution being 1:5, stirring for 4 hours, filtering the precipitate, washing it with water, and drying it at a constant temperature of 100-110° C. for 6 hours. After drying, grinding it and sieving it through a 1000-mesh standard sieve; at the same time, crushing and ball-milling the coal gangue into powder, sieving it through a 1000-mesh standard sieve, and drying it at a constant temperature of 100-110° C. for 6 hours;

[0057] (2) Weighing red mud and coal gangue powder (the proportion of coal gangue added accounts for 50% of the total amount) and placing them in an Ailixu high-power mixer, continuously adding a 3wt% polyvinyl alcohol aqueous solution, the ratio of solution to powder is 75:1 in mL / g, so as to process them into ceramic raw material balls, and then drying the ceramic raw material balls at 30-50°C and sieving them through a 400-mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800°C for 3h to prepare a catalyst matrix;

[0058] (3) Weighing the catalyst substrate and placing it in a 0.02 mol / L nitric acid aqueous solution, stirring and immersing it in a water bath at 40-60° C. for 2 h, the mass ratio of the substrate to the volume of the nitric acid aqueous solution being 1 g:15 ml in g / ml;

[0059] (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h to obtain a motor vehicle exhaust ammonia oxidation catalyst prepared using red mud.

[0060] Example 6

[0061] Solid waste composition for NH 3 Molecular adsorption capacity test:

[0062] Before the ammonia gas TPD test of the catalyst, a certain amount of catalyst powder was squeezed and sieved to form 40 / 60 mesh particles. 1mL to 3mL of the catalyst was weighed and placed in a chemical adsorption instrument. A flow rate of 40mL / min and a concentration of 20% NH 3 Ammonia (Ar as carrier gas) was heated from room temperature to 600°C at a rate of 10°C / min. Figure 1 NH 3 The change in the molecular adsorption area indicates that after adding coal gangue, the catalyst exhibits better ammonia adsorption characteristics, and with the increase in the amount of coal gangue added, the active sites for adsorbing ammonia molecules per unit volume of the catalyst increase significantly, showing better ammonia catalytic oxidation ability, especially when the temperature is lower than 400°C, Example 4 and Example 5 exhibit similar adsorption effects.

[0063] Example 7

[0064] Experimental study on the effect of desorption of ammonia from solid waste composites

[0065] Weigh 1mL to 3mL of catalyst and conduct a reaction test on the introduced ammonia gas through the catalyst activity online evaluation device. The gas condition is a space velocity of 30000h -1 ~60000h -1 , gas composition and concentration NH 3 400ppm~600ppm, the desorption effect of ammonia in Example 1 and Example 4 is as follows Figure 2 shown.

[0066] The above-described embodiments are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field shall fall within the protection scope of the claims of the present invention.

Claims

1. An application of a solid waste composition in adsorbing NH3 molecules, characterized in that: The effective components of the solid waste composition are composed of red mud and coal gangue, wherein the mass ratio of the red mud to the coal gangue is (0.5-1): (0.2-1).

2. The use according to claim 1, characterized in that: The mass ratio of red mud to coal gangue in the solid waste composition is (0.5-0.8):(0.2-0.5).

3. The use according to claim 2, characterized in that: The solid waste composition also includes polyvinyl alcohol and nitric acid.

4. The use according to claim 3, characterized in that: The solid waste composition is prepared by the following method: (1) Red mud is placed in a ball mill, and 0.03-0.05 mol / L of dilute sulfuric acid is added, with a weight ratio of red mud to dilute sulfuric acid of 1:4-1:

6. After stirring for 3-4 hours, the precipitate is filtered and washed with water, and dried at a constant temperature of 100-110° C. for 5-6 hours. After drying, the precipitate is ground and sieved through a 1000-mesh standard sieve; at the same time, the gangue is crushed and ball-milled to form a powder, and then sieved through a 1000-mesh standard sieve, and dried at a constant temperature of 100-110° C. for 5-6 hours; (2) Weighing red mud and coal gangue raw material powders according to the raw material mass (0.5-1): (0.2-1) and placing them in an Eirich intensive mixer, gradually adding a polyvinyl alcohol aqueous solution with a concentration of 1-5 wt% to the mixed raw materials, and the ratio of the solution volume to the raw material mass is (50-100) to (0.5-1) in mL / g, and drying the ceramic raw material balls at 30-50° C. after they are formed, sieving them through a 320-400 mesh standard sieve, and then sintering the dried and sieved raw material balls at a constant temperature of 600-800° C. for 2-3 hours to prepare a catalyst matrix; (3) The catalyst substrate is placed in a nitric acid aqueous solution with a concentration of 0.01 to 0.03 mol / L, and is stirred and immersed in a water bath at 40 to 60° C. for 2 to 3 hours, wherein the ratio of the mass of the catalyst substrate to the volume of the nitric acid aqueous solution is 1:(10 to 20) in terms of g / ml; (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 8-12 hours.

5. The use according to claim 3, characterized in that: The solid waste composition is prepared by the following method: (1) Red mud is placed in a ball mill, 0.04 mol / L of dilute sulfuric acid is added, and the weight ratio of red mud to dilute sulfuric acid is 1:

5. After stirring for 4 hours, the precipitate is filtered and washed with water, and dried at a constant temperature of 100-110° C. for 6 hours. After drying, it is ground and sieved through a 1000-mesh standard sieve; at the same time, the coal gangue is crushed and ball-milled to be powdered, and then sieved through a 1000-mesh standard sieve, and dried at a constant temperature of 100-110° C. for 6 hours; (2) Weighing red mud and coal gangue raw material powder according to the raw material mass (0.5-0.8): (0.2-0.5) and placing them in an Eirich intensive mixer, gradually adding a 3wt% polyvinyl alcohol aqueous solution to the mixed raw materials, and the ratio of the solution volume to the raw material mass is 75:1 in mL / g. After the ceramic raw material balls are formed, they are dried at 30-50°C and sieved through a 400-mesh standard sieve. Then, the dried and sieved raw material balls are sintered at a constant temperature of 600-800°C for 3 hours to prepare a catalyst matrix; (3) The catalyst substrate is placed in a 0.02 mol / L nitric acid aqueous solution, stirred and immersed in a water bath at 40-60° C. for 2-3 h, and the ratio of the mass of the catalyst substrate to the volume of the nitric acid aqueous solution is 1:15 in g / ml; (4) The catalyst substrate is washed with deionized water, and then dried in an oven at 100-110° C. for 10 h.

6. Use of the solid waste composition according to any one of claims 1 to 5 in the preparation of ammonia oxidation catalyst for motor vehicle exhaust.